Strategic steps in promoting gender diversity in South African high schools: A parental perspective on queering cisnormativity - John Chaka; Henry Nichols (International Journal of Studies in Psychology)
It is important to note that transgender learners experienced gender discrimination, misgendering, and bullying at South African High Schools. Based on parental perspectives, this paper presents the strategies that can be used in South African high schools to promote gender diversity. This considers reconceptualisation of gender to enable parents to challenge the factors that act as barriers to the promotion of gender diversity and ensure that the schooling environment is an inclusive one for both trans and cis learners. This paper thus suggests a strategic step that can be used to queer religion and culture to promote gender diversity. This study provides strategies in a three-step guide that parents can use to transform South African high schools into more inclusive environments and to queer cisnormativity.